Model Pemidanaan Terhadap Pelaku Tindak Pidana Korupsi yang Dibarengi dengan Tindak Pidana Pencucian Uang Melalui Platform Digital - Obe, Redentor Goncalinho Antonio; Nay, Florianus Aloysius (Saraq Opat: Jurnal Administrasi Publik, 2022)
The purpose of this study is to describe and find out about the model of punishment for criminal acts of corruption accompanied by money laundering. This research method uses an approach with a normative juridical design approach. Data collection techniques using literature studies as well as data analysis techniques include: (1) presentation, (2) data reduction, and (3) collection and leveraging. The results of the study were: The model for punishing the perpetrators of criminal acts of corruption accompanied by criminal acts of money laundering, which has a predicate crime of corruption on a criminal basis, is in accordance with article 3 of Law Number 8 of 2010 concerning criminal acts of corruption, while in the case of corruption which was accompanied by a criminal act of corruption in the criminal act of the Supreme Court in the results of the meeting of the criminal chamber of the Supreme Court of the Republic of Indonesia, Tangerang No. applying the absorption system is sharpened in accordance with the teachings in article 65 of the Criminal Code. The conclusion of this study is that the teaching about consensus on the results of the meeting of the criminal chamber of the Supreme Court of the Republic of Indonesia in Tangerang has a legal basis that becomes Guinding's guidance/punishment or legal basis in order to be able to revise again the model of punishment that should be given to people who commit crimes involving money and corruption.